Living-lab for people in the Colombian Amazon: a pact for a sustainable territory - Rodriguez, Luz Angela; Vanegas, Martha (2023)
A living-lab for people (LL4P) has been conceptualized as an inclusive and diverse space to design, test, demonstrate and advance sociotechnical innovations and associated modes of governance. While initially proposed within the innovation and communication technologies (ICT), living-labs (LL) have broadened their scope to sectors such as health, cities, public sector, education, and rural development, and now are seen as methodologies or arenas for innovation in which users or citizens play a central and active role. The department of Caquetá, within the Colombian Amazon, is one of the main contributors to land change and greenhouse gas (GHG) emissions in the country due to the functioning of its food systems. Livestock production has been one of the main drivers of environmental change, which is inextricable linked to the model of land occupation based on colonization and extension of the agricultural frontier because of the unresolved issues of land concentration in the interior of the country, the absence of real agrarian reform and the long-term internal armed conflict. Developing a LL4P to support low-emission food systems grounded in local communities’ needs, knowledge, and aspirations could result in social and environmental benefits. Based on the advances in the literature related to agricultural living-labs, and our previous fieldwork and involvement with the communities in the department of Caquetá, we propose to develop a place-based (McPhee et al, 2021), citizens-centered and commons-based (Gamache et al, 2020) agroecosystems living-lab (McPhee et al, 2021), with a focus on inclusion, environmental justice and peacebuilding – something that LL participants have called a “pact for a sustainable territory”. Methodologically, we propose to follow the Participatory Rural Innovation (PRI) approach (Pérez & Clavijo, 2012), through which producers will identify problems and define solutions and innovation routes to build low-emission and sustainable food systems.